Factors Influencing the Acceptance of E-Training Among Faculty Staff at Sebha University: A Structural Equation Modelling Approach - Igrirah, Abdalmunaem; Alafaid, Enbaia (Journal of Pure & Applied Sciences, 2025)
This study investigates the factors influencing the acceptance of e-training among faculty staff at Sebha University using the extended Technology Acceptance Model (TAM2). A total of 74 responses were collected via Google Forms concerning subjective norm, image, job relevance, output quality, result demonstrability, perceived ease of use (PEOU), perceived usefulness (PU), experience, voluntariness, and intention to use. Measurement and structural models were evaluated using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4. Reliability, internal consistency, and validity were confirmed, with Cronbach’s α ranging from 0.776 to 0.929 and AVE values from 0.688 to 0.876, indicating convergent validity. PEOU was found to predict PU, and both PEOU and PU predicted intention to use, albeit with weaker support than the model suggested (β = 0.441, p < 0.001; β = 0.284, p = 0.046; β = 0.314, p = 0.033). No significant effects were identified for subjective norm, image, job relevance, output quality, or result demonstrability. Moderation analysis revealed that experience and voluntariness had no effect on the impact of subjective norm on PU or behavioural intention (all p > 0.05; all f² < 0.01). The model accounted for 66.5% of the variance in PU and 56.6% in intention, highlighting the importance of perceived ease of use and usefulness in the adoption of e-training.